Diagnosis of molar pregnancy and persistent trophoblastic disease by flow cytometry. Issue 6 (June 1987) - Hemming, J D; Quirke, P; Womack, C; Wells, M; Elston, C W; Bird, C C
Abstract : Histopathological assessment and flow cytometric analyses were carried out on 32 placentas (representative of each trimester) and 88 molar pregnancies. Three first trimester placentas were triploid, and the remaining 29 placentas were diploid. Of the 88 cases originally diagnosed as molar pregnancies, 26 were triploid (two complete moles, 20 partial moles, and four hydropic abortions); 59 were diploid (46 complete moles, 10 partial moles, three hydropic abortions); one was tetraploid (partial mole); and two were DNA aneuploid (one partial mole, one complete mole). A significantly increased hyperdiploid fraction (a measure of cell proliferation) was detected in diploid complete moles (p less than 0.0001) and cases of persistent trophoblastic disease (p less than 0.001) when compared with diploid placentas and diploid partial moles. All seven cases of established persistent trophoblastic disease, for which follow up was available, were diploid and showed high hyperdiploid fractions within the range for diploid complete moles. These findings suggest that flow cytometric DNA measurements may be an important aid in the diagnosis of molar pregnancy. The high degree of cell proliferation found in this study may explain the premalignant potential of complete hydatidiform moles.